Topological Optimization as a Factor of Sustainability of Architectural Structures - Myronenko, Viktor; Sopov, Dmytro; ., .; ., . (International Journal of Engineering and Technology, 2018)
It is shown that numerous destruction of buildings and structures under extreme natural impacts (tsunamis, earthquakes, floods, etc.) urgently require revision of existing approaches to their design. It is proposed to use the method of parametric (algorithmic) architecture in the design of buildings and structures operated in extreme weather conditions. It is shown that the algorithmization of the architectural space, subject to chaotic natural effects, is possible with the use of topological optimization methods. n the work used application Autodesk Revit, Grasshopper. As a natural analogue, one of the diatom algae species was selected, which have a light, strong and efficient structure. The project of a floating ecological settlement for 1,5 thousand people is presented. It is shown that with parametric design it is possible to take into account a multitude of factors affecting the construction and, thereby, to increase its resistance to natural disasters.Â Â Â